2022
DOI: 10.3389/fpsyg.2022.816240
|View full text |Cite
|
Sign up to set email alerts
|

Commitment and Wellbeing: The Relationship Dilemma in a Two-Wave Study

Abstract: There has been little consensus around the sequential relationship between organizational affective commitment and workers’ wellbeing. In line with the Conservation of Resources Theory, results of this two-wave study with a contact center employee sample (N = 483) showed that organizational affective commitment decreases work ill-being (i.e., burnout) and increases work wellbeing (i.e., work-engagement). Furthermore, in keeping with the loss spiral assumption of this theory, the mediating role of burnout in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Therefore, according to the results of our study and consistent with the previous literature, well-being at work depends on WFP being accessible (Medina-Garrido et al, 2017) and effectively resolving problems with WFC (Nordenmark & Alm, 2020). Additionally, wellbeing also depends on organizational support (Roemer & Harris, 2018) and the organizational commitment that this support generates in workers (Chambel & Carvalho, 2022;Stevan E. Hobfoll et al, 2018).…”
Section: Moderating Variablessupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, according to the results of our study and consistent with the previous literature, well-being at work depends on WFP being accessible (Medina-Garrido et al, 2017) and effectively resolving problems with WFC (Nordenmark & Alm, 2020). Additionally, wellbeing also depends on organizational support (Roemer & Harris, 2018) and the organizational commitment that this support generates in workers (Chambel & Carvalho, 2022;Stevan E. Hobfoll et al, 2018).…”
Section: Moderating Variablessupporting
confidence: 89%
“…More specifically, previous work has shown a positive correlation between psychological well-being and organizational commitment (Mebarki et al, 2019;Moser & Galais, 2009;Yalçın et al, 2021). In this sense, organizational commitment decreases employees' exhaustion and increases their well-being at work, improving their commitment to their organization (Chambel & Carvalho, 2022). Moreover, there is evidence that employees' commitment to the organization in which they work not only has a direct effect on their well-being, but also on the well-being of their partners (Rodriguez-Muñoz et al, 2014).…”
Section: Organizational Commitment and Well-beingmentioning
confidence: 90%
See 1 more Smart Citation
“…Affective commitment is considered a psychological bond to an organisation and is delineated as positive feelings, affection or emotion towards an organization, bringing back the wish to see the success of organisational goals with pride feelings as related to the organisation (Chambel & Carvalho, 2022;Cohen, 2003). It is also defined as the employees' emotional attachment to identify what is relevant to the organization.…”
Section: Hrm and Organizational Commitmentmentioning
confidence: 99%
“…Individuals committed to the organization will be more accepting of stressful situations and therefore reduce their responses to the added stress (Park & Searcy, 2012). Empirically, affective commitment to the organization has a negative effect on burnout (Chambel & Carvalho, 2022) and negatively affects work stress (Abdelmoteleb, 2019). Setti et al (2016) found that coworker support is positively related to affective commitment, and affective commitment is negatively related to emotional exhaustion.…”
Section: H2: Autonomy Is Negatively Related To Work Stressmentioning
confidence: 99%